Between “modernity” and “postmodernity”: the continuity of coloniality - Saquet, Marcos Aurelio (Revista Campo-Território, 2024)
This text is critical and denounces the disguises used academically and scientifically in discourses called “modern” and “postmodern,” which attempt to appear critical and valid for different times, spaces, and subjects. These narratives claim to be universal and global, and are usually centered on large and complex urban centers, neglecting differences and inequalities, desires and needs, ecosystems and ruralities, contributing to perpetuating North-Eurocentric and colonial approaches. Thus, there is an increasingly urgent need for theoretical and practical subversion, to build our own sciences and philosophies, decolonized, popular, and original, based on the singularities of each time and space, place, and territory, to meet the needs and dreams, in favor of preserving the lives of all.